« Shots in mirrors » : Les jeux de miroir dans No Country For Old Men (Coen 2007) - Julie Assouly (Revue LISA)
In her essay Shots in the Mirror (2000), Nicole Rafter emphasized the appeal of including mirrors in thrillers. More significantly, she described the thriller genre as a mirror of society, thus considering both the object and its metaphorical character. Mirrors are overexploited motifs in film and literature, whose presence scarcely goes unnoticed, begging for a symbolic interpretation. The Coen brothers’ adaptation of No Country For Old Men pays tribute to the many mirrors featured in McCarthy’s novel. The directors exploited the full aesthetic and symbolic potential of the object, from spatiality to its magnifying quality, or uncanny effect. They went beyond the mere inclusion of mirrors by revealing, like Rafter in her essay, their metaphoric dimension, emphasizing the motif of the double, of echo images or « mirrored scene » (Gelly, Ellipses 2021) which appear throughout the film, creating a feeling of déjà vu, yet another occurrence of the uncanny. This article offers to demonstrate how the Coens’ cinematic world, through its use of mirrors, reveals the full potential of McCarthian fantastic/grim fictional universe, creating a hybrid film which seems like a “faithful” adaptation.